Aerospace operations in urban environments : exploring new concepts - Vick, Alan (Rand, 2000)
The recent spate of urban operations in Panama, Somalia, Haiti, and Bosnia has motivated the Department of Defense to put considerable effort into identifying and correcting shortcomings in the United States' ability to successfully conduct urban military operations. Project AIR FORCE undertook a year-long investigation of the role that aerospace forces can play in joint urban military operations. This study sought to help the USAF better understand how the urban physical, social, and political environment constrains aerospace operations, to identify key operational tasks that aerospace forces can help accomplish, and to develop new concepts of operation, including enabling technologies, to enhance the contribution that aerospace forces make to joint urban operations. Among the study's key findings are the following: --Urban areas, with their physical and social complexity, are extremely difficult to operate in. Where possible, U.S. forces should avoid them. --Where urban operations cannot be avoided, aerospace forces can make important contributions to the joint team (air, land, sea, and space forces working together): detecting adversary forces in the open; attacking them in a variety of settings; and providing close support, navigation and communications infrastructure, and resupply for friendly forces. --Offboard sensors for manned aircraft, three-dimensional urban mapping, Global Positioning System relays on unmanned aerial vehicles, and limited-effects weapons have the potential to enhance the ability of aerospace forces to detect and attack adversary forces when rules of engagement are highly restrictive, such as in peace operations, noncombatant evacuations, and humanitarian assistance. Their development should be encouraged. --Automated integration and pattern analysis of inputs from large networks of sensors that use acoustic, infrared, seismic, chemical, and radar detectors will be necessary to interpret the massive volume of activity found in most urban areas. --Practical limitations of automated fusion, coupled with political concerns about collateral damage and civilian casualties, will dictate at least one human decisionmaker remaining in the loop between sensor and shooter, making human-machine interfaces a critical information-architecture issue. This report should be of interest to Air Force personnel in operations, plans, intelligence, and acquisition organizations, and to aviators in the sister services. It is the authors' hope that it will help soldiers, marines, and sailors better appreciate the contribution that aerospace forces can make to joint urban operations.